An Analysis of Alternative Strategy Model for Agroindustry Business Development of Crystal Guava in Malang Raya - I Komang Wahyu Utama Tirta; I Made Sudarma; A. A. Ayu Wulandira Sawitri Djelantik (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2024)
PT. Kreasi Tani Bumiaji is agroindustry company located in Banaran, Bumiaji Village, Bumiaji District, Batu City, East Java. This company focuses on processing agricultural products in the form of crystal guava and becomes a superior local product. This study aimed at analyzing alternative strategy of agroindustry business development of crystal guava as a product in PT. Kreasi Tani Bumiaji. Descriptive-quantitative method was used to collect the primary data from interviews and questionnaire items. Eight participants from the company were selected by using purposive sampling technique. The secondary data were obtained from academic articles. The data were analyzed by using SWOT analysis, Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, Internal-External (IE) Matrix, and QSPM. The results of analysis showed that main internal factor is diversification of processed products with the score 0.277. Meanwhile, external factor is internship collaboration with the score 0.418. The position of company in IE matrix lies on the fifth cell which showed that stable growth with coordinate scores 2.930; 2.594. According to 15 alternative strategies identified using SWOT analysis, prioritized strategy based on QSPM analysis refers to business partnership with investors for the development of production facilities, business concept, and marketing with the highest score 7.23.